Determination of Rational Load of Power Transformers under Conditions of Minimum Power Losses - V. N. Radkevich; A. L. Troushnikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Mathematical expressions have been obtained that allow to determine a number of transformers being operated either in parallel or separately for a common load and ensuring minimum power losses. An electrical load exists in the case of an unequal load of reciprocally reserved transformers. In order to reduce power losses it is expediently to change the number of operating transformers. It has been found out that a value of the load depends on the rate of transformer utilization at the initial mode. In case of load decrease timely transformer trip reduces consumption of active and reactive power as well. Consequently, such trip increases power factor of a consumer load.